Wearable Textile‐Based In‐Plane Microsupercapacitors. Issue 24 (26th August 2016) - Pu, Xiong; Liu, Mengmeng; Li, Linxuan; Han, Shichao; Li, Xiaolong; Jiang, Chunyan; Du, Chunhua; Luo, Jianjun; Hu, Weiguo; Wang, Zhong Lin
Abstract : Solid‐state in‐plane microsupercapacitor is realized on the woven textile substrate for the first time with mask‐aided electroless coating of Ni and hydrothermal reduction of graphene oxides. High capacitive performances, excellent flexibility, and versatile capability in fashionable/comfortable designs are obtained for the application in smart textiles or wearable electronics.